Value-Driven Approach for Project Success and Change Management in Malaysian Institutions of Higher Learning (IHL) - Ammy Amelia Faisal (Institute of Advanced Engineering and Science, 2013)
As a project is a lifeline of any organization, the critical success factors (CSFs) affect the success of the project in project management. This paper provides the literatures and reports as the concept paper which have been made by various researchers regarding the project success factors and change management. The critical success factors which have been applied and brought success to the different organizations will be elaborated in order to identify the factors are applied in Malaysian Institutions of Higher Learning (IHL). Furthermore, the value-driven relationship which consider three project elements, the Business, Project Management Office and Project Team have to be well understood. Lastly, the proposed framework of how the 3 elements mentioned above can lead to the successful in project development implementation which create competitive advantage, will be discussed as for the next step to conduct the empirical study.DOI: http://dx.doi.org/10.11591/ij-ict.v2i2.3351